Natural or replacer sources of milk in lambs during feeding adaptation: influences on performance, metabolism of protein and lipid and oxidative/antioxidant status. Issue 2 (18th May 2016) - Grosskopf, R. K.; Grosskopf, H. M.; Boito, J. P.; Bottari, N. B.; Machado, G.; Biazus, A. H.; Schetinger, M. R. C.; Morsch, V. M.; Tonin, A. A.; Paiano, D.; Balzan, A.; da Silva, A. S.
Summary: This study aimed to evaluate the effect of milk feeding using milk replacer (MR) or natural ewe's milk (NEM) for Lacaune lambs on performance, protein and lipid metabolism and oxidative/antioxidant status. These parameters were evaluated during the period of feeding adaptation, which corresponded to 12 days after ewe's separation. Fifteen lambs were selected and divided into two groups: Group A ( n = 7) with lambs receiving natural milk; Group B ( n = 8) with lambs receiving a milk replacer. Liquid food supply, for both groups, was set according to their body weight, given in two daily periods. Feed intake was also obtained by individual body weight and adjusted according leftovers. Blood samples were collected on three different days (0, 6 and 12) to perform the serum analysis of total protein, albumin, cholesterol, triglycerides, alanine aminotransferase (ALT) and urea. Additionally, the oxidative profile was analysed in sera samples through the assessment of TBARS (reactive substances thiobarbituric acid) and ROS (reactive oxygen species) which aims to identify lipid peroxidation and free radical levels, respectively, as well as the antioxidant profile evaluating glutathione S‐transferase (GST). There was no statistical difference (p > 0.05) between groups on levels of total protein, albumin and globulin. However, cholesterol (day 6), triglycerides (days 6 and 12), urea (day 6) and ALT (day 12) levels differed (p < 0.05) between groups. Values of total protein, globulin, ALT and TBARS differed (p < 0.05) along the time. The average weight gain and body weight differed (p < 0.05) only on day 12, showing that weight gain was higher for lambs fed with NEM. The performance of lambs fed with MR was impaired. Biochemical parameters had a slight variation between groups and along the time, as well as oxidative/antioxidant status did not change in the different liquid diets.